Pengaruh Pelatihan Kader Tanggap Bencana Terhadap Kesiapsiagaan Bencana - Solikhah, Maula Mar’atus; Krisdianto, M. Agung; Kusumawardani, Lita Heni (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2020)
Introduction: Indonesia is geologically vulnerable to disasters until now. Everyone has a potential risk to meet disaster, there for disaster management is somehow important. However, disaster management nowadays often involved related agencies only, but has not involved the society's active role in order to response to disaster emergency. Objective: This aim of this study was to determine the effect of disaster response by cadres training on disaster preparedness in RW 36, Kelurahan Mojosongo Kecamatan Jebres Kota Surakarta Method: This study used quasi experimental design with pre and posttest without control group. A total of 30 cadres were given training for disaster response cadres and their disaster preparedness was measured before and after the training was given. This research instrument used disaster preparedness questionnaire and a flood disaster response module. The data analysis used nonparametric test, namely Wilcoxon test. Results: The results of this study indicate that there was an effect of disaster response training on disaster preparedness with the Wilcoxon Signed Rank Test which result in a p-value of 0.000 (p <0.05). Conclusion:The results of this study were expected to become program innovations for disaster response cadres to increase disaster preparedness